Neonatal Pain : Suffering, Pain, and Risk of Brain Damage in the Fetus and Newborn - Buonocore, Giuseppe; Bellieni, Carlo Valerio (Springer International Publishing : Imprint: Springer, 2017)
This completely revised and updated edition offers a comprehensive overview of neonatal pain assessment and treatment. It includes the field of fetal surgery, and many other topics have been updated or added, such as circumcision analgesia, new drugs, new insights into neurophysiologic pathways of neonatal pain and new drawbacks of analgesic drugs. While in the early years of the 21st century pain treatment in neonates was still optional, it is now a tenet, and more and more institutions are looking for inspiration and good references to create their own guidelines. Written by leading researchers in the field, this book provides that inspiration and offers a valuable tool for neonatologists, anesthetists, nurses and physiotherapists. Since it also deals with prenatal and postnatal surgery, it also appeals to surgeons.